2011
DOI: 10.1007/s11064-011-0514-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Cytokine/Chemokine and Disruption of Blood–Brain Barrier in Neonate Rats After Meningitis by Streptococcus agalactiae

Abstract: We verify the levels of cytokine/chemokine, myeloperoxidase activity, oxidative stress and disruption of BBB in hippocampus and cortex of the neonate Wistar rats after meningitis by S. agalactiae. In the hippocampus the levels were increased of CINC-1 at 6 h and 12 h, IL-1β at 6, 12 and 24 h, IL-6 at 6, 24 and 96 h, IL-10 at 24, 48 and 96 h and TNF-α at 24 h and 96 h. In the cortex the CINC-1 and IL-1β levels were found increased at 6 h. The MPO activity was significantly elevated at 24, 48 and 98 h in hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 47 publications
(62 reference statements)
1
32
0
Order By: Relevance
“…Prior work indicates that inflammatory mediators play an important role in the pathogenesis of experimental traumatic brain injury (Chen et al, 2008). For instance, TNF-a and IL-1b have been shown to affect the integrity of the blood-brain barrier, cerebral edema, and neuronal damage, and participate in the mechanisms of TBI (Barichello et al, 2011;Li et al, 2011;Lloyd et al, 2008). A number of studies have demonstrated that PACAP can modulate inflammatory factor production, including proinflammatory cytokines and ICAM-1, in vivo or in vitro (Armstrong et al, 2008;Arumugam et al, 2009;Reglodi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work indicates that inflammatory mediators play an important role in the pathogenesis of experimental traumatic brain injury (Chen et al, 2008). For instance, TNF-a and IL-1b have been shown to affect the integrity of the blood-brain barrier, cerebral edema, and neuronal damage, and participate in the mechanisms of TBI (Barichello et al, 2011;Li et al, 2011;Lloyd et al, 2008). A number of studies have demonstrated that PACAP can modulate inflammatory factor production, including proinflammatory cytokines and ICAM-1, in vivo or in vitro (Armstrong et al, 2008;Arumugam et al, 2009;Reglodi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Group B streptococcus, S. pneumoniae, and S. suis invade brain microvascular endothelial cells via transcellular mechanisms; however, the associated production of proinflammatory cytokines, the activity of pore-forming toxins, and the induction of plasmin activity may also lead to a concurrent weakening of the BBB, potentially opening a paracellular route of entry. In vivo and in vitro studies have shown that group B streptococci, pneumococci, and S. suis induce the production of a range of cytokines and chemokines, including IL-1␤, IL-6, IL-8, IL-10, TNF-␣, macrophage chemoattractant protein 1 (MCP-1), granulocyte-macrophage colony-stimulating factor (GM-CSF), Gro-␣, and Gro-␤, in brain microvascular endothelial cells (109,(256)(257)(258)) and brain tissue (94,259,260). The stimulation of HBMECs with cytokines (including TNF-␣, IL-1␤, IL-6, and IL-17F) leads to cytoskeletal rearrangements and a redistribution of tight junction and adherens junction proteins, resulting in a decrease in barrier integrity (261)(262)(263)(264)(265)(266)(267).…”
Section: H Influenzae Quagliarello Et Al First Demonstrated That Hmentioning
confidence: 99%
“…This neurotrophin can protect axons, myelin from inflammatory injury and also can modulate the immune system, reducing the magnitude of the excitotoxicity during acute inflammatory activation (Colafrancesco and Villoslada, 2011). Previous study we shown that meningitis by GBS cause oxidative stress, increased of the cytokines/chemokine and BBB breakdown in the first hours after induction (Barichello et al, 2011), a follow up studies of children revealed that, more than ten years after recovery from bacterial meningitis, significant neurological and intellectual impairments still persist (Grimwood et al, 2000). These findings suggest that the meningitis model could be a good research tool for the study of the biological mechanisms involved in the behavioral alterations secondary to GBS meningitis.…”
Section: Discussionmentioning
confidence: 82%
“…Rats underwent a cisterna magna tap with a 23-gauge needle. The animals received either 10 L of sterile saline as a placebo or an equivalent volume of S. agalactiae suspension at a concentration of 1 × 10 6 cfu/mL and were subsequently returned to their cages (Barichello et al, 2011;Trampuz et al, 2007). Meningitis was documented by a quantitative culture of 5 L of CSF obtained by puncture of the cisterna magna (Barichello et al, 2010b).…”
Section: Animal Model Of Meningitismentioning
confidence: 99%